Optimisation of octinyl succinic anhydride starch stablised w1/o/w2 emulsions for oral destablisation of encapsulated salt and enhanced saltiness. (August 2017) - Chiu, Natalie; Tarrega, Amparo; Parmenter, Christopher; Hewson, Louise; Wolf, Bettina; Fisk, Ian D.
Abstract: Sodium (salt) was encapsulated within the inner water phase of w1 /o/w2 food emulsions externally stabilised by starch particles with the ultimate aim of enhancing saltiness perception. The physical properties of the starch particles were modified by octenyl succinic anhydride (OSA) treatment (0–3%) to vary the degree of hydrophobicity of the emulsifying starch. During oral processing native salivary amylase hydrolysed the starch and destabilised the o/w emulsion releasing the inner w/o phase and subsequently sodium into the oral cavity, resulting in a salty taste. Whilst increasing OSA treatment levels increased the stability of the emulsion, intermediate or low levels of starch modification resulted in enhanced saltiness. It is therefore proposed that 1.5% OSA modified starch is optimal for sodium delivery and 2% OSA modified starch is optimal for sodium delivery in systems that require greater process stability. It is also shown that sodium release was further enhanced by oral processing and was positively correlated with native amylase activity. The results demonstrate a promising new approach for the reduction of salt or sugar in emulsion based foods. Graphical abstract: Highlights: The ability of starch modified with OSA (0–3%) to stabilise w1 /o/w2 emulsions was examined. Increasing OSA starch modification improved emulsion stability. Emulsions were perceived to be saltier with a less modified starch as a stabiliser. Intermediate OSA treatment levels are recommended for industrial use. Individual amylase activity affected time to maximum intensity of perception.